Pengaruh Tingkat Pendapatan dan Gaya Hidup terhadap Minat Menabung Masyarakat di Kecamatan Mondokan Kabupaten Sragen - Parni; Harmoyo, Dwi; Mawftiq, Rarasati (Quranomic: Jurnal Ekonomi dan Bisnis Islam, 2022)
This research aimed to determine: 1) how income and lifestyle influence the interest in saving partially, 2) how income and lifestyle simultaneously. The type of research used was quantitative research. The independent variables were income (X1) and lifestyle (X2), the dependent variable was interest in saving as variable Y. The sampling technique in this research was Proportionate Stratified Random Sampling with a sample of 300 respondents from a population of 13,406 Heads of Families, namely the Mondokan District community aged productive and income. The instrument testing technique used validity and reliability tests, tools for instrument testing using Microsoft Excel and SPSS 15. While the data analysis techniques used classical assumption tests, multiple linear analysis, and descriptive analysis. The results showed that: 1) income had an effect on interest in saving with a sig value. 0.018 < 0.050, while lifestyle had no effect on interest in saving with a value of sig. 0.151 > 0.050, 2) income and lifestyle simultaneously affected the interest in saving with a value of sig. 0.026 < 0.050.